Intersecções entre experiências de segurança e ameaça social e modelos de relação interna de autocompaixão e autocriticismo - Pureza, Juliana da Rosa (2020)
Self-compassion and self-criticism are psychological processes that can be considered as internal relationship models, as they refer to the way someone relates to himself in difficult times. Self-compassion is an attitude to cope with suffering and flaws and has been considered a predictor of mental health. Self-criticism is a harsh and judgmental posture adopted in these situations, associated with psychopathologies. Social safeness, the perception of connection and safeness with others, and social comparison, tendency to establish hierarchical and comparative relationships, are also important mental health factors. Self-criticism may be associated with experiences of exclusion and rejection in peer relations and to negative perceptions of social comparison and lower levels offeelings of social safeness, while self-compassion could act as a protective factor for these aspects.The general aim of this thesis was to investigate the intersections between social threat and social safeness and the internal relationship models of self compassion and self-criticism in a Brazilian sample of college students. In the theoretical section, Theoretical Study 1,a book chapter that aimed to trace theoretical associations between self-compassionand bullying experiences in adolescentsis presented.Reflections about the associations between the concepts were discussed, and it is suggested that higher indicators of self-compassion may not prevent bullying situations, but can help adolescents to cope with these experiences. The Theoretical Study 2 aimed to identify associations of self-compassion with experiences of social safeness and social threat through a systematic review. 48 studies that analyzed the relationship between self-compassion and experiences of social threat and social safenesswere found and discussed based on the Social Mentalities Theory. With regard to the empirical section, Empirical Study 1 aimed to validate the Social Safeness and Pleasure Scale to Brazilian portuguese. The sample included 689 Brazilian collegestudents, 493 women, mean age of 27.13 (SD=8.411), who participated in an online survey. A confirmatory factor analysis was carried out and the results confirmed the one-dimensional structure of the scale, which demonstrated adequate indicators of validity and reliability for the total sample and for men and women. The Empirical Study 2 aimed to verify the predictive effects of social safeness and social comparison on the levels of self-compassion and self-criticism. 402 college students participated in this study, and 322 were female, mean age of 25.12 (SD=6.913), who accessed an online survey and completed the Social Safeness and Pleasure Scale, Social Comparison RatigScale and Self-Compassion Scale. The proposed theoretical model was tested through a structural equation modelinganalysis. The results indicated that all paths proposed in the model were statically significant, and that social safeness and social comparison explained 26.5% and 33.6% of the self-compassion and self-criticismvariation, respectively. Finally, the Empirical Study 3 aimed to analyze if there were differences in social comparison, social safeness, self-compassionand self-criticism between normative and sexual minorities groups. The data collection procedures and the sample of this study were the same as in the Empirical Study 2. 328 heterosexual participants form the normative group and 74 lesbian, gay, bisexual participants form the sexual minority group. Comparative analyzes were performed and the results suggest that the sexual minorities groupshowed higher indicators of self-criticism and lower indicators of social safeness and social comparison, but no differences were found regarding to self-compassion. Thus, the general objective of the thesis was achieved, and it was possible to produce theoretical and empirical formulations about the intersections between social threat and social safeness and the internal relationship models of self-compassion and self-criticism. The findings from the five studies can contribute to the promotion of a culture characterized by safe and affective social relationships non-reinforcing of hierarchical and violent relationships, in order to obtain better indicators of mental health and social well-being in different contexts.